THE EFFECT OF SATISFACTION AT WORK IN EMPLOYEE TURNOVER INTENTION - Veranita Chandra; Yedija Christopher William Alexander Margono (Universitas Semarang, 2021)
This literature review is aimed to examine the satisfaction at work and the turnover intention among employees in the Indonesian Banking Sector. The Indonesian banking sector also faces a lot of issues that can affect their performance. One of the major problems that the Indonesian Banking Sector is facing is employee turnover. Job satisfaction has been increasingly valuable in the workplace. Many organizations have now realized that when their employees are happier, their attitudes will be better towards their work. Their motivation will be higher and also, this can impact their performances as well. Therefore, when the employee is loyal to the organization, the turnover rate will decrease because the employee is happy and wants to stay working in the organization. The main objective of this literature review through analyzing three main articles is to analyze the effect of satisfaction at work in Indonesian Banking Sector employee’s turnover intention.Tinjauan pustaka ini bertujuan untuk mengkaji kepuasan kerja dan niat berpindah pada karyawan di Perbankan Indonesia. Sektor perbankan Indonesia juga menghadapi banyak masalah yang dapat mempengaruhi kinerjanya. Salah satu masalah utama yang dihadapi Perbankan Indonesia adalah pergantian karyawan. Kepuasan kerja semakin berharga di tempat kerja. Banyak organisasi sekarang telah menyadari bahwa ketika karyawan mereka lebih bahagia, sikap mereka akan lebih baik terhadap pekerjaan mereka. Motivasi mereka akan lebih tinggi dan juga, ini dapat mempengaruhi kinerja mereka juga. Oleh karena itu, ketika karyawan loyal terhadap organisasi maka tingkat turnover akan menurun karena karyawan tersebut senang dan ingin tetap bekerja di organisasi tersebut. Tujuan utama dari tinjauan pustaka ini melalui analisis tiga artikel utama adalah untuk menganalisis pengaruh kepuasan kerja pada niat berpindah karyawan di industri Perbankan di Indonesia.